A descriptive retrospective audit of the obstetric conditions which occur in mothers of babies with neonatal encephalopathy at Mowbray Maternity Hospital in 2016 - Dietrich, Liesl Bertha Kay (Department of Paediatrics and Child Health, 2020)
Introduction: Neonatal encephalopathy (NE) is an important condition which may result in mortality or severe and permanent morbidity placing much strain on busy under-resourced health care services, parents and families, and the greater community. There is much debate on its aetiology; whether it is caused by antepartum conditions or intrapartum obstetric complications (known as sentinel events); and the relative contribution of intrapartum hypoxia. Unlike perinatal mortality, NE rates are not routinely audited by maternity facilities. At Mowbray Maternity Hospital, a formal audit was conducted in 2008, which measured the NE rate, focussed on obstetric factors associated with NE and identified avoidable factors in the care provided. It was thought to be of clinical value to repeat this audit to identify whether there were any trends in rates and the pattern of obstetric factors. Aims and objectives: The aim was to describe the obstetric factors occurring in patients who delivered neonates at MMH, diagnosed with NE. Specifically, it was planned to determine the NE rate, to describe obstetric factors occurring in these patients and to assess the avoidable factors related to the patients, health system and clinical management. Methodology: This was a retrospective descriptive study which included patients whose neonates were diagnosed with NE and were born at MMH in 2016. The diagnosis of NE was made according to the MMH NE protocol where NE is defined as a voltage suppression in amplitude-integrated electroencephalography (aEEG) or seizures; or clinical seizures or dystonic movements; or moderate to severe clinical signs of NE as defined by Shankaran and a level of consciousness which is decreased with abnormal tone. The neonates’ names were retrieved from a NE register in the neonatal unit and the corresponding mothers’ folders retrieved. Data on relevant obstetric and clinical management factors were collected from the folders using a data collection tool developed in the Western Cape and all cardiotocographic tracings were assessed by the researcher. Ethics approval was granted by the University of Cape Town Human Research Ethics Committee (UCT HREC) prior to the commencement of the study. STATA 14 was used for the analysis. Results: In 2016, 53 neonates with NE were identified out of 9,702 live births (LB) at MMH. The NE rate was 5.5 per 1000 LB. Of the 53 neonates, 48 maternal patient files were retrieved and analysed. There were 58% who had been referred to MMH from the midwife obstetric units (MOUs), and 42% fully managed at MMH. All patients were booked for 14 antenatal care, the mean age was 27.5 years and 50% were nulliparous. The mean gestational age at delivery was 39 weeks. The majority (87.5%) experienced labour, spontaneous in 72.9% and induced in 14.6%. Antenatal complications occurred in 77.1%, the most frequent being prolonged pregnancy (25%) hypertensive disorders (18.8%), antepartum haemorrhage (8.3%) and prelabour rupture of membranes (8.3%). Obstetric problems in labour included prolonged second stage of labour (25% of patients who had a second stage of labour); multiple vaginal examinations (28.6%) and prolonged first stage of labour (17.9%). Fetal monitoring at the MOUs was done according to protocol in 70% of patients in the latent phase but only 12.5% of those in the active phase of labour. At MMH, all patients in labour had Cardiotocograph (CTG) monitoring with 90.6% of CTGs being pathological and 6.3% suspicious, as assessed by the researcher. Meconium stained liquor occurred in 40.5% of patients. The mode of delivery was normal vertex, (27.1%), Caesarean sections (58.3%) and assisted vaginal delivery (14.6%). Most CS (71.4%) were done for pathological CTGs. Sentinel events occurred in 15 (31.3%) patients; approximately two-thirds occurring intrapartum and one- third antenatal. Sentinel events included shoulder dystocia (10.4%), prolonged second stage of labour (10.4%), abruptio placenta (6.3%), cord prolapse (2.1%) and eclampsia (2.1%). Of the 37 (68.7%) without a sentinel event, 75.8% had a pathological CTG. Considering avoidable factors, there was an ambulance delay in 42.9%, and a delay in accessing theatre for 53.6% of patients requiring a CS. Poor quality CTG tracing and monitoring occurred in 20.8% of patients; and for 34.4%, the researcher identified an abnormal CTG but it was not detected by the attendant health care workers. Discussion and conclusion: The NE rate for MMH is 5.5 per 1000 LBs, this is higher than the 3.7 found in the previous 2008 MMH study, despite a higher CS rate. Possible reasons for the increase include changes in case ascertainment, increased workload with same staff component, or a shift from perinatal hypoxic mortality to morbidity, notably NE. This NE rate compares with other lower resource settings and the previous MMH audit, as does the high proportion of intrapartum obstetric sentinel events. This is in contrast to findings from high resource settings. Areas for service improvement include regular and ongoing intrapartum care training, including fetal heart monitoring, for medical and nursing staff; and addressing the health system issues identified.